Anti–Interleukin‐6 Receptor Tocilizumab for Severe Juvenile Idiopathic Arthritis–Associated Uveitis Refractory to Anti–Tumor Necrosis Factor Therapy: A Multicenter Study of Twenty‐Five Patients. Issue 3 (27th February 2017) - Calvo‐Río, Vanesa; Santos‐Gómez, Montserrat; Calvo, Inmaculada; González‐Fernández, M. Isabel; López‐Montesinos, Berta; Mesquida, Marina; Adán, Alfredo; Hernández, María Victoria; Maíz, Olga; Atanes, Antonio; Bravo, Beatriz; Modesto, Consuelo; et al.
Abstract : Objective: To assess the efficacy of tocilizumab (TCZ) for the treatment of juvenile idiopathic arthritis (JIA)–associated uveitis. Methods: We conducted a multicenter study of patients with JIA‐associated uveitis that was refractory to conventional immunosuppressive drugs and anti–tumor necrosis factor (anti‐TNF) agents. Results: We assessed 25 patients (21 female; 47 affected eyes) with a mean ± SD age of 18.5 ± 8.3 years. Uveitis was bilateral in 22 patients. Cystoid macular edema was present in 9 patients. Ocular sequelae found at initiation of TCZ included cataracts (n = 13), glaucoma (n = 7), synechiae (n = 10), band keratopathy (n = 12), maculopathy (n = 9), and amblyopia (n = 5). Before TCZ, patients had received corticosteroids, conventional immunosuppressive drugs, and biologic agents (median 2 [range 1–5]), including adalimumab (n = 24), etanercept (n = 8), infliximab (n = 7), abatacept (n = 6), rituximab (n = 2), anakinra (n = 1), and golimumab (n = 1). Patients received 8 mg/kg TCZ intravenously every 4 weeks in most cases. TCZ yielded rapid and maintained improvement in all ocular parameters. After 6 months of therapy, 79.2% of patients showed improvement in anterior chamber cell numbers, and 88.2% showed improvement after 1 year. Central macular thickness measured by optical coherence tomography in patients with cystoid macular edema decreased from a mean ± SD of 401.7 ± 86.8 μm to 259.1 ± 39.5 μm after 6 months of TCZ ( P = 0.012). The best‐corrected visual acuity increased from 0.56 ± 0.35 to 0.64 ± 0.32 ( P < 0.01). After a median follow‐up of 12 months, visual improvement persisted, and complete remission of uveitis was observed in 19 of 25 patients. Significant reduction in the prednisone dosage was also achieved. The main adverse effects were severe autoimmune thrombocytopenia in 1 patient, pneumonia and then autoimmune anemia and thrombocytopenia in 1 patient, and viral conjunctivitis and bullous impetigo in 1 patient. Conclusion: TCZ appears to be a useful therapy for severe refractory JIA‐associated uveitis.